Multi-frequency aerodynamic control of a yawed bluff body optimized with a genetic algorithm. Issue 212 (May 2021) - Qiao, Z.X.; Minelli, G.; Noack, B.R.; Krajnović, S.; Chernoray, V.
Abstract : This experimental work aims to investigate the manipulation of a bluff body flow with a yaw angle of 10° based on a genetic algorithm optimization. Two loudspeakers are used to generate zero-net mass-flux jets through streamwise slots, which span a large portion of the rounded A-pillars of the bluff body. The actuations produce a maximum drag reduction of 17% and 2% for the leeward and windward side control, respectively. The genetic algorithm has found two typical frequencies to separately drive the actuators on the windward and leeward sides. The drag reduction is 20% under the optimal control law, 3% larger than the 17% attained from the reference single frequency control. In addition, a beneficial effect is observed when considering energy efficiency, which increases by 30% in the optimal control compared to the single frequency control. The drag spectra and velocity mapping in the wake are measured with and without control, and, based on the measurement, the underlying flow mechanism behind the control is proposed. Highlights: The genetic algorithm provides a useful tool for bluff-body turbulence control at a yaw angle. The optimization of genetic algorithm obtains a 20% drag reduction, 3% larger than the single frequency control. The energy efficiency increases by 30% in the optimal control compared to the single frequency control.